Screening and interaction study of the operating parameter influence the wax formation using design of experiment - Norida, Ridzuan; Subramanie, P.; Elarbe, B. S.; Elganidi, I.; Kumar, S. D. V. (Universiti Malaysia Pahang, 2020)
Oil and gas industry has been facing the wax deposition issue due to low temperature condition during the transportation of crude oil from offshore to onshore. The most common method to overcome this problem is by injecting polymeric wax inhibitor in the pipeline. The aim of this work is focused on the screening of the factors that affect the wax deposit inhibition using two types of wax inhibitor; which are poly(ethylene-co-vinyl acetate) (EVA) and Petronas-pour point depressant (PPD) through Design Expert software version 7.1.6. The other three factors evaluated include cold finger temperature (5 & 20℃), rotation speed of impeller (100 & 600 rpm) and the duration of experiment (2 & 6 h). Sixteen experiments were run to observe the rate of wax deposition using cold finger apparatus suggested by level of factorial analysis. The results revealed a significant model with R2 value of 0.989 indicating that 98.9% of the variable response can be explain d by the model. From the analysis of variance (ANOVA), factor D, which has the addition of EVA in crude oil was found to be the main factor affecting the wax deposit inhibition followed by duration of the experiment, rotation speed, cold finger temperature and Petronas-PPD factors. Furthermore, the interaction between factor D (EVA) and factor E (Petronas –PPD) shows the greatest influence to reduce wax deposition. The best configurations to minimize the amount of wax deposit were found using standard order No 1 which is at 5℃, 100 rpm and for the duration of 2 h using EVA as wax inhibitor. The amount of wax deposit measured is 0.018g. Hence, it can be concluded that factor D, and interaction between factors D and E need to be focused in controlling the parameters to minimize wax deposition.